Ultrastructural and morphometric aspects of ageing in the retinal capillaries of rats - Schellini, Silvana Artioli [UNESP]; Gregório, E. A. [UNESP]; Padovani, Carlos Roberto [UNESP]; Spadella, César Tadeu [UNESP]; Moraes-Silva, M. A. [UNESP] (My University, 1997)
Age-related morphological, ultrastructural and morphometric changes in the capillaries of the superficial and deep plexuses of the rat retina were studied in animals aged from 3 to 15 months. Our results suggest that age-related morphological alterations start occurring in the retina of rats at about 12 months of age. Increased glycogen deposits, pinocytotic vesicles, residual bodies and cell debris were observed in both the endothelial and pericytic cells of 12- and 15-month-old animals. In addition, heterogeneous osmiophilic accumulations, electron-transparent spaces were observed in the basement membrane as well as projections of the basement membrane towards the neighboring cells. Morphometric examination of the two vascular plexuses studied did not show differences in the area of the endothelial or pericytic cells, basement membrane or vascular lumen between rats of different ages.
Keywords: Ageing; Morphometry; Rat; Retinal vessels; Ultrastructure; aging; animal; capillary; electron microscopy; growth, development and aging; muscle development; rat; retina blood vessel; ultrastructure; vascular endothelium; vascular smooth muscle; Wistar rat; Aging; Animals; Capillaries; Endothelium, Vascular; Microscopy, Electron; Muscle Development; Muscle, Smooth, Vascular; Rats; Rats, Wistar; Retinal Vessels